Administrative creativity and its relationship to career maturity from the perspective of employees of the Directorates of Physical and Technical Education in Iraqi Universities - Ramzi Rafeeq, Shaheen; Al-Ahmady, Waleed Amer Dhayee (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The aim of this study was to identify the level of the areas of administrative creativity, the level of the dimensions of career maturity, as well as the relationship between administrative creativity and career maturity from the perspective of the employees of the Directorates of Physical and Technical Education in Iraqi universities. A descriptive approach was used (survey method) due to its relevance with the nature of the research, and the sample consisted of 128 employees of the Directorates of Physical and Technical Education in Iraqi Universities. The researchers used two questionnaires to measure the administrative creativity and career maturity (the Administrative Creativity Questionnaire and the Career Maturity Questionnaire). After verifying the validity and reliability of the study instruments, the data were processed using the Statistical Program for the Social Sciences (SPSS). The employees of the Directorates of Physical and Technical Education in Iraqi universities possess a high level of administrative creativity, an average level of career maturity, and the absence of a statistically significant relationship between the areas of administrative creativity and the dimensions of career maturity (p > 0.05), except for the emergence of a negative significant relationship between career planning and creativity (p < 0.05, r = -*0.289). The researchers recommend encouraging employees to face challenges and demonstrate their creativity, and not to marginalize the employees in the planning process and decision-making.